Censorship detected in JO (Jordan) - Voidly (Voidly Global Censorship Index, 2025)
CRITICAL severity censorship detected in Jordan. Data sourced from CensoredPlanet.
Censorship Incident ID: JO-2025-0001. Severity: critical. Confidence: 75%